Servicio de directorio basado en código abierto en el GADM del cantón Junín - Vera Castro, Jojar Baruc (2017)
The present work focused on improving the accessibility of Information Technology (IT) resources in the Junín GADM, through the implementation of a directory service, because it is important for the institution that the workforce can access the different technological resources from any area within the establishment. For the implementation of Zentyal 5.0 (directory service) the cascade methodology was used, the same one that through the stage of communication allowed to analyze the existing structures and components as well as determining the requirements of the entity, then in the planning and modeling the best solution was chosen according to the needs presented, later in the construction the operational test of the server was realized in a controlled environment, finally in the deployment proceed with the implementation of the service in the institution. The result obtained is the application of a technological tool that contributes to the organization and security of the documents that are handled within the aforementioned GADM.